Prostitution Practices of Elderly Commercial Sex Workers in the Perspective of Social Bonds Theory (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
This article discusses about the social control among community towards the practice of prostitution from elderly commercial sex workers in the Pamulang area, South Tangerang by using social bonds theory with 4 main components, namely attachment, commitment, involvement, and belief. This research was conducted within 5 months in Pamulang, South Tangerang. The subjects of this research amounted to 5 resource persons, namely 3 commercial sex workers, 1 surrounding community, and 1 party from the South Tangerang Social Service. This research implements qualitative approach by descriptive method, with primary and secondary data sources. The result shows that the community is aware about the social deviation of prostitution practice around them, then they reject it by giving a warning. The involvement of community leaders who act as pimps encourages the community to be permissive. The permissive attitude that arises is due to economic factors and weak community conditions. The weak relationship with the family and never making an example of the mistakes she experienced by continuing to choose a job as a commercial sex worker until her elder age. This makes the social control of the community that occurs in the Pamulang area, South Tangerang weak and the practice of prostitution of elderly prostitutes will continue to occur.